The Effect of Conspicuous Consumption Behavior on Wasteful Consumption Behavior: The Intermediary Role of Hedonic Consumption Behavior - İbrahim Avcı (Journal of Economy Culture and Society, 2022)
The concept of consumption, which has an important place in people's lives, is generally expressed as the use of produced goods and services in line with needs. Consumption now includes the psychological needs of people as well as their physical needs. Consumers can buy things they do not need by acting pleasure-orientedly, and they exhibit consumption behaviors to provide psychological satisfaction. One of the consumer-purchase patterns is found to demonstrate others in the social environment. Therefore, non-need consumption focused on pleasure and display causes excessive consumption; this situation can also cause wastefulness. Accordingly, in the present study, the aim was to examine the effect of conspicuous consumption behavior on wasteful consumption behavior and the mediating role of hedonic consumption behavior in this effect. With the online survey form prepared, 519 participants were reached between the dates of 21.05.2020-06.07.2020. The data obtained were analyzed with the SPSS 21, AMOS 24, and PROCESS 3.5 programs. After the analysis, it was concluded that conspicuous consumption behavior has an effect on wasteful consumption behavior and that hedonic consumption behavior has a mediating effect.